2015
DOI: 10.1007/s10508-015-0644-8
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Objectifying Media Consumption, Objectification of Women, and Attitudes Supportive of Violence Against Women

Abstract: A recent White House Council Report on Women and Girls called attention to sexual assault on college campuses and encouraged continued research on this important public health problem. Media that sexually objectify women have been identified by feminist scholars as encouraging of sexual assault, but some researchers question why portrayals that do not feature sexual assault should affect men's attitudes supportive of violence against women. Guided by the concepts of specific and abstract sexual scripting in Wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 60 publications
6
85
0
Order By: Relevance
“…Our findings alert researchers to the need for additional investigations in this line of research, as some studies that have examined the influence of music videos on adolescents and young adults have included samples where Black men make up less than 10% of the study population (Aubrey, Hopper, & Mbure, 2011;Wright & Tokunaga, 2016;Zhang, Miller, & Harrison, 2008). Researchers conducting empirical studies should be intentional in working to include Black men in their samples.…”
Section: Implications and Future Directionsmentioning
confidence: 90%
“…Our findings alert researchers to the need for additional investigations in this line of research, as some studies that have examined the influence of music videos on adolescents and young adults have included samples where Black men make up less than 10% of the study population (Aubrey, Hopper, & Mbure, 2011;Wright & Tokunaga, 2016;Zhang, Miller, & Harrison, 2008). Researchers conducting empirical studies should be intentional in working to include Black men in their samples.…”
Section: Implications and Future Directionsmentioning
confidence: 90%
“…An infrequently investigated—but often discussed—third category is nonviolent but objectifying and degrading pornography (Kingston et al, ; Seto et al, ). Not explicitly violent, but nevertheless dehumanizing, depictions may also affect aggressive attitudes and disinhibit aggressive behaviors (Wright & Tokunaga, ). In their meta‐analyses, Allen and colleagues found that experiments in which investigators classified content as “nonviolent” did not result in a statistically weaker aggressive response (Allen et al, , p. 271) or, across all experiments, a statistically weaker increase in ASV (although content labeled “violent” produced a stronger effect than content labeled “nonviolent” within studies that included both conditions; Allen et al, , p. 19).…”
Section: Previous Meta‐analysesmentioning
confidence: 99%
“…We know of its potential for causing harm, in particular to psychosocial wellbeing, potential for the objectification of women, and for generating harmful negative stereotypes (see e.g. Perrin et al 2008;Wright and Tokunaga 2016); we also know that it has been found to increase risky sexual behaviour (Jonas et al 2014;Eaton et al 2012). Our review brought up many such studies.…”
Section: Getting Down To It: What Does Research Into Porn Tell Us?mentioning
confidence: 99%
“…Some studies have, to some extent, overcome this by triangulating data from different sources; for example Jonas et al (2014), who describe an association between viewing risky practices -in this case 'bareback' 2 porn -and safe sex intentions, conducted two separate studies, one online and the other in a sex club, in order to reach their conclusions. However, a recent study by Wright and Tokunaga (2016), published in the wake of a globally prominent case of campus sexual assault, used a 'volunteer' population of university students and an online survey to assess the relationship between 'men's objectifying media consumption' and 'attitudes supportive of violence against women'. Although the paper does not describe how volunteers were recruited, it does make mention of the possibility of reverse causality (i.e.…”
Section: Getting Down To It: What Does Research Into Porn Tell Us?mentioning
confidence: 99%